CT measures of adrenal gland length and caudal pole diameter are reproducible in large breed dogs: A pilot study. Issue 4 (8th April 2021) - Perfetti, Simone; Diana, Alessia; Baron Toaldo, Marco; Cipone, Mario; Quinci, Manuela; Pey, Pascaline
Abstract: Computed tomography (CT) is increasingly available to evaluate dogs with suspected adrenal disease, however, published studies describing the reproducibility of CT methods for quantifying adrenal gland (AG) measurements are lacking. This prospective, pilot, observer agreement study aimed to evaluate reproducibility and repeatability of two different methods of measurement of AGs on CT to establish a usable technique and define standard reference ranges. Multiplanar reformatted (MPR) CT images of both AGs of six large breed dogs were obtained with the MPR axis parallel to the spine and parallel to the long axis of the AG. Ten measurements were performed: maximal length and diameter at cranial and caudal poles on dorsal, sagittal, and transverse images; and minimal diameter of cranial and caudal poles on transverse images. Three observers with different levels of experience repeated these measurements three times for each dog. Intra‐ and interobserver variability were calculated through intraclass correlation coefficient (ICC). The differences in time to perform measurements between the two methods were tested with Student's t ‐test. Regardless of the measurement method used, length of AGs on dorsal and sagittal MPR images had the lowest intra‐ and inter‐observer variability (ICC = 0.93‐0.99), diameter of caudal pole on transverse plane showed low intra‐ and interobserver variability (ICC = 0.77‐0.80) and diameter of cranial pole had the highest variability (ICC = 0.12‐0.61). Although length was the less variable measurement, its use may be unrealistic in daily practice. Interestingly measurement of caudal pole on transverse plane was characterized by low intra‐ and interobserver variability. No difference in time performing the measurements was noted between the two methods.